Unusual manifestations of acute Q fever: autoimmune hemolytic anemia and tubulointerstitial nephritis - Korkmaz Serdal; Elaldi Nazif; Kayatas Mansur; Sencan Mehmet; Yildiz Esin (BMC, 2012)
Abstract Q fever is a worldwide zoonotic infection that caused by Coxiella burnetii, a strict intracellular bacterium. It may be manifested by some of the autoimmune events and is classified into acute and chronic forms. The most frequent clinical manifestation of acute form is a self-limited febrile illness which is associated with severe headache, muscle ache, arthralgia and cough. Meningoencephalitis, thyroiditis, pericarditis, myocarditis, mesenteric lymphadenopathy, hemolytic anemia, and nephritis are rare manifestations. Here we present a case of acute Q fever together with Coombs' positive autoimmune hemolytic anemia (AIHA) and tubulointerstitial nephritis treated with chlarithromycin, steroids and hemodialysis. Clinicians should be aware of such rare manifestations of the disease.